Empowering primiparous mothers with e-coaching for enhanced self-efficacy in postpartum and newborn care - Fatmawati, Ariani; Dewi, Inggriane Puspita; Syabariyah, Sitti; Ridlayanti, Annisa (Jurnal Ners, 2025)
Introduction: Postpartum challenges pose significant stress and diminish maternal confidence among first-time mothers. These challenges are exacerbated by limited healthcare access, cultural influences, and logistical barriers, which complicate postpartum self-management, particularly in resource-constrained settings. Addressing these issues is essential. Methods: The study employed an explanatory sequential mixed-methods design. The initial phase involved a quasi-experimental survey to compare self-efficacy scores between intervention and control groups, each consisting of 30 participants. Self-efficacy was measured using the Perceived Maternal Parenting Self-Efficacy (PMP S-E) scale, and the Mann-Whitney test was employed to compare group means. The second phase was a qualitative study. Participants from the intervention group were selected using simple random sampling based on odd-numbered identifiers, resulting in 15 primiparous women. Data were analyzed using thematic analysis. Results: Participants in both groups had comparable age distributions and educational backgrounds.  The intervention group achieved a significantly higher mean score (65) compared to the control group (41.8), confirmed by a Mann-Whitney test (p < 0.001) with a large effect size (Cohen's d = 5.15). Qualitative findings identified five themes and 15 categories. Conclusions: E-coaching effectively enhances maternal self-efficacy in primiparous mothers, offering a promising approach to addressing postpartum challenges in resource-limited settings.